Little women - Alcott, Louisa May, 1832-1888; Alcaraz, Marie Frances (Quezon City : Lampara Publishing House, 2011)
"Little women follows the lives of the four March sisters growing up during the civil war. Money is scarce, and their father is away serving as a minister in the army, but pretty Meg, tomboyish Jo, shy Beth and precocious Amy, with the guidance of their beloved Marmee and the invaluable friendship of Laurie, the boy next door, strive to make the very best of it. They fill their days with shared adventure and learning, and Jo would prefer things to remain the way they are, but when love begins to bloom for Meg, their father falls ill, and Beth catches the scarlet fever, they all must come to terms with change."--Cover
Keywords: Sisters -- Fiction; New England -- History -- 19th century -- Fiction; Domestic fiction